Analysis of Raw Material Inventory Control Using the Min-Max Stock Method to Control Inventory Costs at PT. Artha King Indonesia - Ramadhan, Ardana; Saifuddin, Joumil Aidil (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
In the current era of globalization, a company must always try to have the ability to compete with other companies. The issue of inventory planning and control is one of the most important things every business has to face. This study aims to determine the picture of inventory management using Min-Max Stock at PT Artha King Indonesia and find out the amount of inventory costs incurred using the Min Max Stock method. The type of research used is quantitative descriptive research conducted at PT Artha King Indonesia. We recommend that data collection uses primary data from interviews and company observations. While secondary data is obtained from historical company data. The results of this study show that theoretically the minimum and maximum limit values of stock, safety stock, and reorder level (Q) are different for each raw material. Furthermore, by using a policy proposal with the minimum inventory method, the cost calculation results show that the annual costs incurred by the company are lower because there is no excess or out-of-stock material during the warehouse period. Knowing the results of theoretical calculations of the above values, it is possible to evaluate the policies used today so that in the future the company can minimize the costs incurred and maximize profits.